Adult Diffuse Low-Grade Gliomas: 35-Year Experience at the Nancy France Neurooncology Unit - Obara, Tiphaine; Blonski, Marie; Brzenczek, Cyril; Mézières, Sophie; Gaudeau, Yann; Pouget, Celso; Gauchotte, Guillaume; Verger, Antoine; Vogin, Guillaume; Moureaux, Jean-Marie; Duffau, Hugues; Rech, Fabien; et al. (Frontiers in Oncology, 2020)
Background. To report survival, spontaneous prognostic factors and treatment efficacy in a French monocentric cohort of diffuse low-grade glioma (DLGG) patients over 35 years follow-up. Methods. A monocentric retrospective study of 339 patients diagnosed with a new DLGG between 01/01/1982 and 01/01/2017 was created. Inclusion criteria were patient age ≥ 18 years at diagnosis, histological diagnosis of WHO grade II glioma (according to 1993, 2007 and 2016 WHO classifications). The survival parameters were estimated using the Kaplan-Meier method with a 95% confidence interval. Differences in survival were tested for statistical significance by the log-rank test. Factors were considered significant when p ≤ 0.1 and p ≤ 0.05 in the univariate and multivariate analysis respectively. Results. A total of 339 patients were included with a median follow-up of 8.7 years. The Kaplan-Meier median overall survival was 15.7 years. At the time of radiological diagnosis, Karnofsky Performance Status score and initial tumor volume were significant independent prognostic factors. Oncological prognostic factors were the extent of resection for patients who underwent surgery and the timing of radiotherapy for those concerned. In this study, patients who had delayed radiotherapy (provided remaining low grade) did not have worse survival compared with patients who had early radiotherapy. The functional capabilities of the patients were preserved enough so that they could remain independent during at least three quarters of the follow-up. Conclusion. This large monocentric series spread over a long time clarifies effects of different therapeutic strategies and their combination in the management of DLGG.